ONLINE PET PRODUCTS MANAGAMENT SYSTEM - J. Leena Rose; R. Meenaloshini (Galaxy International Interdisciplinary Research Journal, 2022)
The undertaking named "Online Pet Products Management System" created by PHP as Front End and MYSQL as Back End. This task is about the offer of pet items Clients utilize their client id and secret word to log in to the framework.